Knowledge, attitude, and practices of cattle farmers regarding zoonotic diseases in Erzurum, Turkey - Özlü, Hayrunnisa; Atasever, Mustafa; Atasever, Meryem Aydemir (Austral Journal of Veterinary Sciences, 2020)
This study aimed to determine the knowledge, attitude, and practices of cattle farmers regarding zoonotic diseases in Erzurum, Turkey, where cattle-raising is the most common occupation. A cross-sectional study was conducted on 1,045 cattle farmers in Erzurum. In terms of the diseases that can be transmitted from animal to human, 69.6% of the cattle farmers had information on anthrax, 62.8% on brucellosis, 18.4% on tuberculosis, 44.9% on rabies, 32.5% on Crimean-Congo hemorrhagic fever, 8.9% on hydatid cyst, 8.0% on toxoplasmosis and 7.9% on giardiasis. The knowledge level of cattle farmers who were university graduates was 94.8%. Cattle farmers having over 100 cattle had a knowledge level of 96.7% on zoonotic diseases and their positive attitudes and practices reached 95.1% and 91.8%, respectively. The results showed that the increase in education status, size of the enterprise, and monthly income of cattle farmers was related to an increase in knowledge, attitude, and practices regarding zoonotic diseases. However, it was found that the positive knowledge and attitudes of the cattle farmers could not be transformed into positive practices evenly.